Transcriptome analysis and immune gene expression of channel catfish (Ictalurus punctatus) fed diets with inclusion of frass from black soldier fly larvae - Sankappa, Nithin Muliya; Lange, Miles D.; Yildirim-Aksoy, Mediha; Eljack, Rashida; Kucuktas, Huseyin; Beck, Benjamin H.; Abernathy, Jason W. (Frontiers in Physiology, 2024)
The larval waste, exoskeleton shedding, and leftover feed components of the black soldier fly and its larvae makeup the byproduct known as frass. In this study, we subjected channel catfish (Ictalurus punctatus) to a 10-week feeding trial to assess how different dietary amounts of frass inclusion would affect both systemic and mucosal tissue gene expression, especially in regard to growth and immune related genes. Fish were divided in quadruplicate aquaria and five experimental diets comprising 0, 50, 100, 200, and 300 g of frass per kilogram of feed was fed twice daily. At the end of the trial, liver, head kidney, gill, and intestine samples were collected for gene expression analyses. First, liver and intestine samples from fish fed either a no frass inclusion diet (control), a low frass (50 g/kg), or a high frass (300 g/kg) inclusion diet were subjected to Illumina RNA sequencing to determine global differential gene expression among diet groups. Differentially expressed genes (DEGs) included the upregulation of growth-related genes such as glucose-6-phosphatase and myostatin, as well as innate immune receptors and effector molecules including toll-like receptor 5, apolipoprotein A1, C-type lectin and lysozyme. Based on these initial screenings of low/high frass using RNA sequencing, a more thorough evaluation of immune gene expression of all tissues sampled, and all levels of frass inclusion, was further conducted. Using targeted quantitative PCR panels for both innate and adaptive immune genes from channel catfish, differential expression of genes was identified, including innate receptors (TLR1, TLR5, TLR9, TLR20A), proinflammatory cytokines (IL-1β type a, IL-1β type b, IL-17, IFN-γ, and TNFα), chemokines (CFC3 and CFD), and hepcidin in both systemic (liver and head kidney) and mucosal (gill and intestine) tissues. Overall, frass from black soldier fly larvae inclusion in formulated diets was found to alter global gene expression and activate innate and adaptive immunity in channel catfish, which has the potential to support disease resistance in this species in addition to demonstrated growth benefits.